Experimental evaluation of nanoclay assisted water based EOR method - Hamid Mohammad Soleimani; Mohammad Taghi Sadeghi (Journal of Petroleum Exploration and Production Technology)
Abstract Recently, one of the most applicable nanoparticles (NPs) is nanoclay that is especially used in drilling to enhance the rheology of the drilling fluids. However, the experimental analysis of nanoclay in enhanced oil recovery (EOR) applications was rarely investigated. The main goal of this study is to find an ideal nanoclay concentration for the EOR fluid in two steps. The first is nanoclay stability that focus on finding the most stable nanofluid and the second is interfacial tension (IFT) and contact angle (CA) measurement that concentrate on selecting the best EOR fluid. Experiments such as nanofluid preparation, nanofluid stability, Dynamic Light Scattering (DLS), Zeta potential, X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM) analysis, clay swelling tests, CA and IFT measurements were performed for this purpose. All of the experiments were done in ambient pressure and temperature. The core samples and thin sections that are used in the experiments are oil-wet in nature. Results of the experiments confirm the stability of nanoclay in presence of the selected surfactant Cetyl Trimethyl Ammonium Bromide (CTAB) employed in the study. On the other hand, nanoclay has the ability to reduce the IFT nearly 5 dyne/cm, and also the combination of nanoclay and CTAB modify CA in the order of 10. It is founded that the optimum concentration for EOR fluid during the experiments is 0.5 weight% (wt%) CTAB and 0.1 wt% nanoclay.